2013
DOI: 10.1002/cphc.201300257
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Spin Relaxation and Translation Diffusion in Liquids and Polymer Melts: Insight from Field‐Cycling1H NMR Relaxometry

Abstract: With the advent of commercial field-cycling (FC) spectrometers, NMR relaxometry has gained new momentum as a method of investigating dynamics in liquids and polymers. The outcome of FC NMR experiments is spin-lattice relaxation time versus frequency (relaxation dispersion). In the case of protons, due to the intra- and intermolecular origin of dipolar interactions, the relaxation dispersion reflects rotational as well as translational dynamics. The latter shows a universal dispersion law at low frequencies, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 51 publications
2
89
0
Order By: Relevance
“…Indeed, as anticipated above, it has been shown that the intermolecular contribution to R 1 (ω) must not be ignored suggesting that the exponent α might also be influenced by the intermolecular relaxation [13,16,17,25]. Moreover, the intermolecular relaxation is an important source of information regarding translational dynamics in polymer melts.…”
Section: Full Dipolar Correlation Function In Polymer Meltsmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, as anticipated above, it has been shown that the intermolecular contribution to R 1 (ω) must not be ignored suggesting that the exponent α might also be influenced by the intermolecular relaxation [13,16,17,25]. Moreover, the intermolecular relaxation is an important source of information regarding translational dynamics in polymer melts.…”
Section: Full Dipolar Correlation Function In Polymer Meltsmentioning
confidence: 89%
“…As a continuation of the pioneering work of Kimmich and collaborators [7] the dynamics of linear polymers such as 1,4-polybutadiene (PB) with different M has been studied by field-cycling (FC) 1 H NMR relaxometry [13,15,19,24,[55][56]. Transforming the measured relaxation rates Applying FTS the correlation loss is probed over nine decades in time and eight in amplitude.…”
Section: Full Dipolar Correlation Function In Polymer Meltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulsed and static field gradient NMR techniques can be classified as direct ones because the diffusion coefficients are determined directly from the NMR signal attenuation, recorded as a function of the magnetic field gradient strength and/or the time at which the diffusion is followed. Recently, the fast field-cycling (FFC) NMR relaxometry technique has been also successfully used for characterization of the translational diffusion, especially in liquid and soft systems [4,26,27,31,32]. This indirect and non-gradient method gives the possibility to determine the diffusion coefficient from measured frequency dependency (dispersion profile) of spin-lattice relaxation time by applying a suitable theoretical model describing the dynamics of the molecules (ions).…”
Section: Introductionmentioning
confidence: 99%
“…Translational dynamics of particles (molecules or ions) has fundamental meaning for all important transport processes occurring in micro-scale in nature and therefore is extensively explored in different molecular systems [1][2][3][4]. For ionic liquids (ILs), the translational modes of the molecular dynamics of ions potentially provide the information on interionic interactions or molecular rearrangements reflecting complex diffusion processes associated, among others, directly with ionic conductivity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%